Literasi Dalam Al-Qur’an: Tinjauan Tematik Tafsir Al-Mishbah - Maisyarah, Pupungawi; Amalih, Ihwan (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2023)
The Qur'an also contains a lot of wisdom and learning. Literacy is one of the ways in the Qur’an. Literacy is very important in society or at school because reading and writing are indirect ways of communicating, while speaking and listening are direct communication. Writing is a way of communicating by expressing thoughts, ideas, feelings, and wishes to others in writing. This study uses a qualitative approach with the type of library research, which is a critical and in-depth study of library materials that are relevant to the research theme. In this analysis the researcher found that M. Quraish Shihab in the book of Al-Mishbah commentary explained that surah Al-Alaq was the first revelation revealed to the Prophet Muhammad SAW, through the intermediary of the angel Gabriel as. In the first verse of Surah Al-Alaq, the revelation that came down contained an order to read. The term إقرأ which is found at the beginning of this verse has various meanings, including reading, studying, researching and other meanings, all of which boil down to the meaning of gathering.